TOKSISITAS DAN KEMAMPUAN ANESTETIK MINYAK CENGKEH (Sygnium aromaticum) TERHADAP BENIH IKAN PELANGI MERAH (Glossolepis incisus) - Saskia, Yayu; Harpeni, Esti; Kadarini, Tutik (Jurusan Perikanan dan Kelautan, 2013)
The research of cloves oil (Sygniumaromaticum) as anesthetic materialto rainbow fish (Glossolepis incisus) wasinvestigated with the lethal concentration(LC50-48 hours), effective concentration (EC50-1 hours), time passed out and recovery timeafter conscious. Data analysis by usingprobit was conducted to find out the valueof LC_50-48 and linear regression analysisused to find recovery time after conscious.The results showed that LC50-48 hours valueis 0,273 ml/L and EC50-1 hours valueis 0,159 ml/L. Cloves oil at concentrations0,159 ml/L was used as anesthetic within50% rainbow fish stock during 40,02 minutesand time to recovery is 3,54 minutes.